2011
DOI: 10.3855/jidc.1660
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasites and genotypes of Giardia intestinalis in school children from Berisso, Argentina

Abstract: Introduction: Intestinal parasitic infections have been reported in different regions of Argentina. Giardia intestinalis is recognized as "the national parasite". The aim of this work was to determine the prevalence of both intestinal parasites and G. intestinalis genotypes, as well as to analyze the clinical and epidemiological characteristics in schoolchildren from a suburban community. Methodology: Serial coproparasitological analysis and perianal swab method were performed in 244 schoolchildren. Demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
1
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 39 publications
4
14
1
11
Order By: Relevance
“…Assemblage B was seen to be predominant (42 of 69 or 61%) with group BIII the most common of the four genotypes (26 or 38%). This is in agreement with previous studies (Amar et al 2002, Bertrand et al 2005, Lebbad et al 2008, Minvielle et al 2008, Aldana et al 2011, Molina et al 2011). Assemblage A was found in 22 of the 69 isolates (32%) with group II (19 of 69 or 28%) the most common.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Assemblage B was seen to be predominant (42 of 69 or 61%) with group BIII the most common of the four genotypes (26 or 38%). This is in agreement with previous studies (Amar et al 2002, Bertrand et al 2005, Lebbad et al 2008, Minvielle et al 2008, Aldana et al 2011, Molina et al 2011). Assemblage A was found in 22 of the 69 isolates (32%) with group II (19 of 69 or 28%) the most common.…”
supporting
confidence: 94%
“…Assemblage BIV was found in 16 (23%) and only three individuals were infected with Group AI (4%); this low frequency is consistent with the literature (Amar et al 2002, Bertrand et al 2005, Babaei et al 2008). Interestingly, five individuals (7%) in this study were co-infected with both genotypes AII and BIII, which also has been previously documented (Amar et al 2002, Babaei et al 2008, Molina et al 2011). Overall, the odds ratio (OR) of diarrhoea in individuals infected with Giardia, compared to those uninfected, was 3.11 (95% CI = 2.11, 5.10).…”
supporting
confidence: 87%
“…Entre las especies halladas, Blastocystis sp., E. vermicularis y G. lamblia fueron las más frecuentes en la mayoría de las provincias, en concordancia con otras investigaciones (14, 32, 35). Entre las provincias estudiadas, la mayor frecuencia de Blastocystis sp.…”
Section: Discussionunclassified
“…In a third stage, the program measures the impact of those interventions. Among the previous published research from the project, Molina et al (2011) found the presence of intestinal parasites in suburban schoolchildren was associated only with house flooding. A multivariate analysis identified G. intestinalis was correlated with use of latrine.…”
Section: Methodsmentioning
confidence: 99%